Developing Creativity In Early Childhood Using Nature Based Media - Putri Novryanti Nesimnasi; Kevi Stevani Nokas; Maria Marsanda Mego; Delfi Natalia Baunsele; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Background: Creativity is a fundamental aspect of early childhood development because it supports children's ability to think creatively, solve problems, explore their environment, and express original ideas. Nature-based learning has been widely recommended as an experiential approach that provides meaningful opportunities for exploration and creativity. Objective: This study aimed to examine the effect of nature-based media on the creativity of children aged 4–6 years at TK Cemara Liliba. Method: This quantitative study employed an ex-post facto research design involving 16 children selected through purposive sampling. Data were collected using structured questionnaires and observation sheets measuring the implementation of nature-based media and children's creativity. Instrument validity and reliability were established prior to data collection. Data were analyzed using descriptive statistics and simple linear regression with SPSS version 25.0. Results: The findings showed that nature-based media contributed 12.3% of the variance in children's creativity (R² = 0.123). However, the relationship was not statistically significant (F = 1.966; p = 0.183 > 0.05), indicating that children's creativity was largely influenced by other factors beyond the scope of this study. Novelty: This study provides empirical evidence regarding the implementation of nature-based media in an authentic early childhood education setting while demonstrating its limited independent contribution to creativity development. Conclusion: Nature-based media can enrich children's learning experiences, but its effectiveness should be strengthened through inquiry-based activities, teacher guidance, and collaboration with families to optimize creativity development.